2017
DOI: 10.4103/0971-9784.197842
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed therapy improves the outcome of high-risk cardiac patients undergoing off-pump coronary artery bypass

Abstract: Background:There has been a constant emphasis on developing management strategies to improve the outcome of high-risk cardiac patients undergoing surgical revascularization. The performance of coronary artery bypass surgery on an off-pump coronary artery bypass (OPCAB) avoids the risks associated with extra-corporeal circulation. The preliminary results of goal-directed therapy (GDT) for hemodynamic management of high-risk cardiac surgical patients are encouraging. The present study was conducted to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“… 13 A recent study concluded that gold-directed therapy decreases duration of inotropic support in high-risk cardiac patients undergoing off-pump coronary artery bypass. 14 …”
Section: Discussionmentioning
confidence: 99%
“… 13 A recent study concluded that gold-directed therapy decreases duration of inotropic support in high-risk cardiac patients undergoing off-pump coronary artery bypass. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Some of those additional factors contributing to this finding may include patient pathology, condition, higher EBL, epidural vasoplegia, and greater insensible loss typical of more complex surgery as previously noted, though this result remains difficult to interpret in such a broad and multifactorial setting. Nevertheless, the variables affecting this previous result, namely, possible different ASA classifications among the AM vs. PM patient groups [4,16,17], the possible differential epidural placement for different cases [18,19], the possible difference in the number of laparoscopic procedures in the AM vs PM groups [20,21], different possible urine loss in cases of differing nature [22,23], possible different patient demographics in weight [23][24][25] or in age [26][27][28], the different pragmatic scheduling need for surgical procedures of longer duration in the AM vs the PM groups [29][30][31], and the possible different hemodynamic heat rate parameter between surgical cases of different nature among the AM vs PM groups [21,32,33], have all been accounted for in the literature with evidence showing the clear benefit of following the GDFT algorithm. In some regards these limitations result from and are common to how operating rooms actually run.…”
Section: Discussionmentioning
confidence: 99%
“…Some of those additional factors contributing to this finding may include patient pathology, condition, higher EBL, epidural vasoplegia, and greater insensible loss typical of more complex surgery as previously noted, though this result remains difficult to interpret in such a broad and multifactorial setting. Nevertheless, the variables affecting this previous result, namely, possible different ASA classifications among the AM vs. PM patient groups [16][17][18] , the possible differential epidural placement for different cases [19][20] , the possible difference in the number of laparoscopic procedures in the AM vs PM groups [21][22] , different possible urine loss in cases of differing nature [23][24] , possible different patient demographics in weight [25][26][27] or in age [28][29][30] , the different pragmatic scheduling need for surgical procedures of longer duration in the AM vs the PM groups [31][32][33] , and the possible different hemodynamic heat rate parameter between surgical cases of different nature among the AM vs PM groups [34][35][36] , have all been accounted for in the literature with evidence showing the clear benefit of following the GDFT algorithm. In some regards these limitations result from and are common to how operating rooms actually run.…”
Section: Discussionmentioning
confidence: 99%